The Materialization Characteristics and Ratio of a New Soil Paste Filling Material - Zhi Wang; Weijian Yu; Fangfang Liu (Advances in Civil Engineering)
In this paper, the research background is the filling and mining of the landscape mineral paste body in Baixian State, Guangxi, China. The strength test of the new paste filling material is carried out by the materials of coal zircon, red soil, and cement, the best ratio between the materials is obtained, and the hydration mechanism of the new paste filling material is studied by XRD diffraction instrument and SEM (scanning electron microscopy) test. The types of hydration products and microstructure forms of filling materials in different age periods are revealed. The test results show that the optimal ratio of the new paste filling material in the coal mine is the quality ratio of coal zircon: red soil: cement as 6 : 2 : 1, and the slurry concentration is 80%, which can not only meet the transportation requirements required by the filling process but also reduce the cost of filling, and with the extension of the maintenance age, the filling material produces more gel products, and the overall structure is more encrypted.